The Effect of Physical Work Environment in The Flexibility of Industrial Operations - داود غسان قاسم; عباس سجى رياض (Journal of Economics and Administrative Sciences, 2012)
he research specifies important subjects which contribute in improvement of productive performance in industrial companies through study and analysis of relationships and effect between dimensions of physical work environment and industrial operations flexibility in the leathers industries company. To reach these goals the information are collected is questionnaire prepared for this purpose as a tool to analyze the practical results and are recorded for a sample of 118 persons from employees. The research uses the statistical methods and analyzes the information by using SPSS system. The research reached to many conclusions; the important one is the weakness of the company to make in to account the physical environment to improvement of efficiency and flexibility of its industrial operations. The research ended by many suggestions one of the most important is the importance of improvement of operation places and design of tools and machines suitable to improve the operational efficiency for the production apparatuses.